IMPROVING STUDENTS' MOTIVATION AND READING SKILLS IN ELT THROUGH AUDIO VISUAL MEDIA - As Sabiq, Agus Husein (Diksi, 2017)
This research aims to describe: (1) the use of audio-visual media in teaching and learning in English class, (2) the use of audio-visual media in improving the motivation and reading skills of the seventh-grade students of MTs Al Iman Purworejo. This research is classroom action research which used Kemmis & McTaggart model with two cycles. The subjects were students of class VII D of MTs Al Iman Purworejo in the academic year of 2014/2015. The objects were the audio-visual media, and students' motivation and reading skills in English. The results of this study show that the use of audio-visual media improved 90% of the students to have a high motivation in English class that includes attitude, interest, and effort in learning English. In addition, the use of audio-visual media also improved 83% of the students to gain their reading skills achievement of descriptive text to get scores higher than the minimum standards. The result of the pretest showed 57% of students had high motivation, in the first cycle there were 70% of students who had high motivation, and in the second cycle there were 90% of students who had high motivation. The students' reading skill also improved; in the initial test 48% of students had scores higher than the minimum standard; in the first cycle, there were 65% of students having scores higher than the minimum standard, and; in the second cycle, there were 83% of students having scores higher than the minimum standard. Thus, it can be concluded that the use of audio-visual media can improve the motivation and reading skills in English lessons of class VII D students' of MTs Al Iman Purworejo.Keywords: motivation, reading skill, audio-visual media MENINGKATKAN MOTIVASI DAN KETERAMPILAN MEMBACA SISWA PADA PENGAJARAN BAHASA INGGRIS MELALUI MEDIA AUDIO-VISUAL ABSTRAKPenelitian ini bertujuan untuk  mendeskripsikan: (1) penggunaan media audio-visual dalam proses belajar mengajar di kelas bahasa Inggris, (2) penggunaan media audio-visual dalam meningkatkan motivasi dan kemampuan membaca siswa kelas VII MTs Al Iman Purworejo. Penelitian ini adalah tindakan kelas yang menggunakan model Kemmis & McTaggart dengan dua siklus. Subjek penelitian adalah siswa kelas VII D MTs Al Iman Purworejo tahun akademik 2014/2015. Objek penelitian ini adalah media audio-visual, motivasi dan kemampuan membaca siswa pada pelajaran bahasa Inggris. Hasil penelitian ini menunjukkan bahwa penggunaan media audio-visual meningkatkan 90% dari siswa untuk memiliki motivasi tinggi terhadap kelas bahasa Inggris yang meliputi sikap, keinginan, dan usaha dalam belajar bahasa Inggris. Selain itu, penggunaan media audio-visual juga meningkatkan 83% dari siswa untuk mendapatkan prestasi kemampuan membaca pada teks deskripsi dengan mendapatkan nilai lebih dari standar minimal. Pada uji awal, 57% siswa memiliki motivasi tinggi, pada siklus pertama terdapat 70% siswa memiliki motivasi tinggi, dan pada siklus kedua terdapat 90% siswa memiliki motivasi tinggi. Kemampuan membaca siswa juga mengalami peningkatan dimana pada tes awal terdapat 48% siswa mendapat nilai diatas standar minimal, pada siklus pertama terdapat 65% siswa mendapat nilai diatas standar minimal, dan pada siklus kedua terdapat 83% siswa mendapat nilai diatas standar minimal. Dengan demikian disimpulkan bahwa penggunaan media audio-visual dapat meningkatkan motivasi dan keterampilan membaca pada pelajaran bahasa Inggris siswa kelas VII D MTs Al Iman Purworejo.Kata Kunci: motivasi, keterampilan membaca, media audio-visual